EVALUATION OF THE CHILD SAFETY EDUCATION COALITION IN ENGLAND. (7th October 2012) - Mulvaney, C; Watson, M; Errington, G; Coupland, C; Kendrick, D; Walsh, P
Abstract : Background: In 2008 the Royal Society for the Prevention of Accidents was awarded £1.6m from the UK government to establish the Child Safety Education Coalition (CSEC). CSEC's role was to improve 'the provision of practical safety education to give more children and young people the skills, knowledge and confidence to keep themselves safe'. Aims/Objectives/Purpose: A team from the University of Nottingham evaluated CSEC in terms of:  its processes, such as establishing the coalition and working with partners  its impact on increasing the provision of practical safety education  its impact on those determinants of unintended injury which are amenable to change through practical safety education. Methods: Multiple data collection methods were used: interviews of members, non-members and stakeholders, observations of meetings, questionnaires surveying members' practical safety education provision, case studies of members to illustrate practice, and international expert review of CSEC's achievements and future potential. Results/Outcome: CSEC attracted a diverse membership of 129 organisations. Collaborative working facilitated the exchange of ideas. CSEC coordinators worked with members to develop the Resource Profiler and the Risk Competency Frameworks which members used to evaluate and improve their practical safety education and consequently the safety knowledge and skills of children. This collaboration also established new opportunities for providing practical safety education. Significance/Contribution to the Field: Coalitions provide a useful forum for members to enhance their own practice by learning from the experience of others. In the long term national coalitions have the potential to positively influence the provision of practical safety education.